Comparison of Ultrasound-Guided Transversalis Fascia Plane Block, Quadratus Lumborum Block, and Ilioinguinal-Iliohypogastric Block for Postoperative Analgesia in Cesarean Section - A, Bhargavi.; kumar, G. Chaitanya; Jakkam, Chaitanya; chaitanya, K. Krishna; Prabhavathi, R.; teja, A. Charan (Journal of Neonatal Surgery, 2025)
Background: Postoperative pain is a common complication after caesarean section (CS), and its management is essential to prevent adverse perioperative outcomes. Well-managed postoperative analgesia improves patient comfort while encouraging early ambulation and breastfeeding. This study aims to compare the analgesic efficacy of transversal fascial plane block (TFPB) vs. quadratus lumborum block (QLB) vs. Ilioinguinal Iliohypogastric (ILIH) block in patients undergoing caesarean section under neuraxial anaesthesia. Methods And Materials: In this randomized clinical trial, 90 patients undergoing elective CS under spinal anesthesia were randomly allocated to receive TFPB or QL, or ILIH block under ultrasound guidance after surgery. The severity of pain was assessed using Visual Analogue Scale (VAS) during rest at 0, 2, 4, 6, 12, and 24 hours after surgery, time to ﬁrst analgesic request, and dosage of analgesic use and complications were compared between groups. Results: The cumulative paracetamol consumption over 24 hours was 1 gram for the QL group, 1 to 1.5 grams for the TFP group, and > 2 grams for the ILIH group. The median paracetamol consumption at 12 hours and 16 hours was also lower in the QL group compared to the TFP and ILIH groups (P <0.05). There was no statistically signiﬁcant difference between groups regarding time to ﬁrst analgesia request (p >0.05). The pain scores at 18 hours and 24 hours were lower in the QL group compared to the TFP and ILIH groups, respectively (p <0.05). There is no statistically signiﬁcant difference between groups regarding the postoperative side effects and complications. Conclusion: In all three QLB, TFPB had comparable high analgesic efficacy during the first 24 hours. QL block had longer analgesic effectiveness compared to TFPB and ILIH block, with an effect lasting for 18- 24 hours.